Advances in the treatment of autosomal recessive congenital ichthyosis, a look towards the repositioning of drugs - Peña-Corona, Sheila I.; Gutiérrez-Ruiz, Stephany Celeste; Echeverria, Ma de los Dolores Campos; Cortés, Hernán; González-Del Carmen, Manuel; Leyva-Gómez, Gerardo (Frontiers in Pharmacology, 2023)
Autosomal recessive congenital ichthyoses (ARCI) are a skin pathology due to genetic causes characterized by a variable degree of desquamation, accompanied by erythema. The degree of symptoms is variable, different altered genes are involved, and the symptoms drastically affect patients' quality of life. Topical treatments are a first-choice strategy due to their ease of application and cost; however, enteral administration of retinoids offers greater efficacy, although with certain limitations. Despite the treatment alternatives, ARCI will persist throughout life, disabling people. Therefore, the search for new treatments always remains necessary. Especially repositioning drugs could be a short-term alternative to new affordable treatments for patients. Taking advantage of extensive knowledge of known drugs or biologics could ensure more accessible and possibly lower-cost treatments. This review briefly and concisely addresses possible repositioning strategies with drugs and biologics for ichthyosis.